Small Supernumerary Marker Chromosome (sSMC) 15 in Male Primary Infertility: A Case Study - Filomena Mottola; Renata Finelli; Veronica Feola; Kristian Leisegang; Lucia Rocco (Case Reports in Medicine)
This case report describes a 39-year-old phenotypically normal male patient of a married couple with primary infertility presenting as candidates for assisted reproductive techniques. The medical history of the couple is unremarkable, with both partners phenotypically normal. Semen analysis revealed oligoasthenzoospermia (OAT), 15% sperm DNA fragmentation and 4% aneuploidies in the sperm nuclei. Genetic analysis showed no Y chromosome of cystic fibrosis transmembrane conductance regulator gene mutations. Karyotype analysis in the male partner revealed a small supernumerary marker chromosome (sSMC) derived from chromosome 15, specifically inverted and duplicated (inv dup(15)) corresponding to the 15q11.2 region but lacking the Prader-Willi/Angelman syndrome critical region (PWACR). Further investigations revealed that 35% of the patient’s spermatozoa carried the sSMC(15). This case study highlights the potential association between the presence of an inv dup(15) sSMC, without the involvement of the PWACR, and male infertility. sSMC(15) may disrupt spermatogenesis and contribute to oligoasthenozoospermia in males with primary infertility. Further research into the association of mechanism mechanisms of male infertility related to the 15q11.2 region is warranted.